High performance hiring - Wendover, Robert W. (Crisp Pub. Menlo ParkUS, 1991)
Explains legal aspects of hiring (in the USA); suggests how to find appropriate applicants; and explains applicant selection procedures. Provides guidelines for orientation, and training; and one sample each of a rejection letter, and a letter of offer.